Implementing grassroots inclusive change through a cultural audit. Issue 3 (10th September 2018) - Selzer, Robin; Foley, Todd
Abstract : Purpose: The purpose of this paper is to implement diversity and inclusion practices in an USA university department through the application of a cultural audit in the style of participatory action research (PAR). The cultural audit process demonstrates an inclusive, grassroots approach to creating actionable solutions that brings about positive organizational change and can be replicated by others. Design/methodology/approach: The version of an organizational cultural audit described here included two phases. The first was quantitative in nature, using a survey to collect data that would provide the organization with a perspective of how its culture is perceived (Fletcher and Jones, 1992) and serve as the basis for the second, more crucial phase. The second phase utilized PAR qualitative approach. Having data presented in aggregate form allows for truer reactions to how others believe they experience the work environment, as opposed to making assumptions about how others may experience the work environment. A cultural audit such as this relies heavily upon the qualitative narrative that is exposed when participants react to the quantitative data presented. In fact, the real assessment begins not with the quantitative data collection process, but with the presentation of the quantitative data and the analysis of how participants respond to what they see. Findings: The researchers found social and practical implications for empowering employees to develop a culturally agile organization. Results showed that participants generally viewed the culture as lacking transparency and needing values-based guidelines for everyday interactions. Participants thought they should value diversity, but viewed the culture as having a gap in solutions to apply that value. Incentivizing actions that promote diversity and inclusion and better shared governance were needed to address cultural problems in the organization. Recommendations for actionable solutions included: developing shared language through a values statement, restructuring onboarding and mentoring support, increasing transparency of standing committee work, membership, and minutes to foster trust and communication, implementing group guidelines for respectful interactions, and the creation of regular, planned social events to enhance human relations. This case study is significant because it uses an innovative method to not only study diversity and inclusion in a university setting, but also take action, thereby filling a gap in the literature on critical studies of organizations. Research limitations/implications: For those trying to institute a similar experience for their organization, it would be important to note that the cultural audit was a grassroots intervention, designed to help the division discern what kinds of lived experiences and shared assumptions exist within. Practical implications: The case study presented should serve as a roadmap for how individuals can garner support for conducting a similar cultural audit with their own organizations. Originality/value: This case study is significant because it uses an innovative method to not only study diversity in a university setting, but also take action, thereby filling a gap in the literature on critical studies of organizations.